Advances of Various Heterogeneous Structure Types in Molecular Junction Systems and Their Charge Transport Properties. Issue 30 (17th August 2022) - Shin, Jaeho; Eo, Jung Sun; Jeon, Takgyeong; Lee, Takhee; Wang, Gunuk
Abstract: Molecular electronics that can produce functional electronic circuits using a single molecule or molecular ensemble remains an attractive research field because it not only represents an essential step toward realizing ultimate electronic device scaling but may also expand our understanding of the intrinsic quantum transports at the molecular level. Recently, in order to overcome the difficulties inherent in the conventional approach to studying molecular electronics and developing functional device applications, this field has attempted to diversify the electrical characteristics and device architectures using various types of heterogeneous structures in molecular junctions. This review summarizes recent efforts devoted to functional devices with molecular heterostructures. Diverse molecules and materials can be combined and incorporated in such two‐ and three‐terminal heterojunction structures, to achieve desirable electronic functionalities. The heterojunction structures, charge transport mechanisms, and possible strategies for implementing electronic functions using various hetero unit materials are presented sequentially. In addition, the applicability and merits of molecular heterojunction structures, as well as the anticipated challenges associated with their implementation in device applications are discussed and summarized. This review will contribute to a deeper understanding of charge transport through molecular heterojunction, and it may pave the way toward desirable electronic functionalities in molecular electronics applications. Abstract : The authors present recent advances to develop a wide spectrum of molecular heterostructures, as well as their prospects and applicability. Various molecular heterostructures and their novel electrical characteristics, along with their charge transport mechanisms are presented. In addition, the potential applicability, merits, and perspectives, as well as the anticipated challenges associated with their implementation in electronic device applications are discussed.